Nuove parentele e memoria della migrazione marocchina in Italia - Maher, Vanessa (L’Uomo società tradizione sviluppo, 2022)
It is difficult to view migratory experience, which is often transnational, within a conventional frame of social memory, such as, for example, that of national history, emblem of the twentieth century. On the other hand the experience of «double absence», (the term which Sayad used to refer to the way the migrant lacks a recognized social role both in his country of origin and in that to which he has emigrated) makes it difficult for the migrant to feed his personal recollections into a shared memory which can be transmitted to others. For some authors, this processing of personal recollections is a function and necessary aspect of kinship ties (Carsten 2007). Life in a new country may make a migrant‟s recollections more incoherent, giving rise to the sensation of living in parallel temporalities. This paper will focus on the way new kinds of relatedness are constituted in the country of immigration, which , through new ritual forms and ways of conferring meaning on places and events, serve as workshops of memory, in which experience can be interpreted and construed, allowing for the creation of a new relationship between individual recollections and social memory. Even the anthropologist may sometimes be called upon to contribute to this process.